Broken harbor [large type] - French, Tana (French, Tana. Dublin Murder Squad series, 2012)
In the aftermath of a brutal attack that left a woman in intensive care and her husband and young children dead, brash cop Scorcher Kennedy and his rookie partner, Richie, struggle with perplexing clues and Scorcher's haunting memories of a shattering incident from his childhood.